Perkembangan Sektor Industri terhadap Penyerapan Tenaga Kerja dan Produk Domestik Regional Bruto (PDRB) pada Sektor Industri di Provinsi Kalimantan Selatan - Danu Amparian; S Saipudin; Ika Chandriyanti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
This research aimed to analyze the effect of industrial business units and labor wages (as an indicator of the industrial sector) on the labor absorption and Gross Regional Domestic Product (GRDP) in the industrial sector in South Kalimantan Province. The research employed secondary data collected from time series to see the data developed during the period from 1998 to 2018. These data were then analyzed using the path analysis method. The results revealed that the industrial business units and labor costs have a significant effect on employment. Furthermore, the industrial business unit variables did not have a direct, significant influence on the GRDP of the industrial sector. A significant effect was also found between labor wages and labor absorption on the GRDP of the industrial sector. In an indirect manner, the labor absorption variable acts as an intermediary for the influence of the industrial business unit variable on the GRDP of the industrial sector. Meanwhile, in the effect of the labor wages on the GRDP of the industrial sector, the labor absorption variable does not act as an intermediary. Generally, labor wages have a greater effect on the GRDP of the industrial sector than the variables of industrial business units. Interestingly, a different conclusion was revealed by Nunung (2018) that the minimum wage in her research does not have a significant impact on employment in Central Java Province because there are companies that set wages below market prices. Furthermore, Rochmani et al. (2016) reported that the number of industrial business units does not positively impact labor absorption because industrial conditions in Central Java Province are labor-intensive. Therefore, labor absorption is not affected by the presence or absence of business units